Mali : Staff Report for the 2005 Article IV Consultation, Second and Third Reviews Under the Poverty Reduction and Growth Facility, and Request for Waiver of Nonobservance of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2006)
This paper discusses Mali's 2005 Article IV Consultation and Second and Third Reviews Under the Poverty Reduction and Growth Facility (PRGF). The PRGF-supported program is broadly on track. Performance on quantitative aspects remains strong. Although the record on the structural program has been disappointing, the program for 2006 would mark significant progress on addressing key challenges. The IMF staff supports the authorities' request for completion of the second and third reviews under the arrangement and waivers for nonobservance of three structural performance criteria.